The Existence Of The Islamic Economy In Building The World of Education - Choiriyah Choiriyah; Dwi Noviani; Mardeli Mardeli (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
Islamic economics is one of the economic concepts that should be considered to replace it. Islamic economics has made a lot of progress, both in the operational practice of academic studies in universities and in the form of teaching activities. Islamic economics has been developed in several universities both in Muslim countries and in western countries. In the context of Indonesia, the development of learning and implementation of Islamic economics has made significant progress. It is proven by learning about Islamic economics that has been taught in several public and private universities. This proves that the increase in human resources and the Islamic development economy continue to grow.